2005
DOI: 10.1016/j.jvs.2005.07.040
|View full text |Cite
|
Sign up to set email alerts
|

In situ aortic allograft insertion to repair a primary aortoesophageal fistula due to thoracic aortic aneurysm

Abstract: Aortoesophageal fistula due to thoracic aortic aneurysm is an uncommon cause of gastrointestinal bleeding and has an extremely poor prognosis. In the English literature, we found only 27 successfully managed cases of primary aortoesophageal fistula due to thoracic aortic aneurysm. We present a case of 74-year-old man who experienced the erosion of a thoracoabdominal aortic aneurysm into the esophagus. We successfully performed resection and replacement of the thoracoabdominal aorta with a cryopreserved allogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…From our experience, we agree with others that conservative management is of no help especially in non-compliant patients like ours. [8,9] In our patient, esophageal exclusion and debridement were considered the best management followed by restoration of esophageal continuity with gastric pull-up. We used a pectoral myocutaneous flap for secondary esophageal reconstruction when anastomotic dehiscence at the upper anastomosis of the gastric pull-up had occurred.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…From our experience, we agree with others that conservative management is of no help especially in non-compliant patients like ours. [8,9] In our patient, esophageal exclusion and debridement were considered the best management followed by restoration of esophageal continuity with gastric pull-up. We used a pectoral myocutaneous flap for secondary esophageal reconstruction when anastomotic dehiscence at the upper anastomosis of the gastric pull-up had occurred.…”
Section: Discussionmentioning
confidence: 86%
“…[2] Thoracic CT is the most important tool in diagnosis and planning for management. [8] Management should not be delayed once AOF is diagnosed. Management consists of two essential parts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some surgeons, such as Burks, Pirard, Topel, and others [5][6][7], consider repairing aortic defect of AEF by endovascular stent should be seemed as a transitional measure before definitive open surgery. Or even, Prokakis et al suppose that endovascular stent grafting should be limited only to patients who are at high risk for open surgical repair [8].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some authors suggested that an endovascular stent graft should only be used in patients with a high risk of open surgery [2,6] . Since 2005, Pirard et al [7,8] have attempted to combine endovascular with open surgical approach, which brings more hope to decrease the mortality of AEF.…”
Section: Discussionmentioning
confidence: 99%